Development of the 8-Item Phlegm Pattern Questionnaire (PPQ-8) Using Rasch Analysis. (28th October 2021) - Park, Young-Jae
Abstract : The 25-item Phlegm Pattern Questionnaire (PPQ) has been widely used to examine the relationship between the phlegm pattern (PP), quality of life, tongue colour, vocal qualities, and dysfunctional breathing. However, the concerns of response burden and differences in the respondent's abilities or item difficulty for the original version of the PPQ have not been sufficiently addressed. This study aimed to develop a short-form PPQ using Rasch analysis, an item response theory. Based on the retrospective data, the response order, differential item functioning (DIF), dimensionality, reliability, concurrent validity, and fitting errors were examined for 291 normal participants and 61 inpatients. The discriminative ability of the short-form PPQ was examined using receiver operating characteristic curve analysis. Along with Rasch analysis, another short-form PPQ was developed using equidiscriminative item-total correlation (EITC) analysis and the results between the two short-form PPQs were compared accordingly. Rasch analysis results suggested a 6-point response category for the PPQ, and finally, 8 items without fitting errors or DIF variability were selected for the PPQ (PPQ-8). The PPQ-8 had satisfactory reliability (person separation index = 2.23), unidimensionality (unexplained variance in the first contrast = 1.598), fitting levels (infit mean square, 0.80–1.39; outfit mean square, 0.79–1.34), sensitivity (70.5%), and specificity (76.5%). The PPQ-8 had a moderate discriminative ability of the PP (area under the curve = 0.759), and the cut-off point was 23. Although the 8-item PPQ developed using EITC analysis showed similar levels of reliability, validity, and discriminative ability of the PP to the PPQ-8, it could not present the information of item hierarchy and differences in the respondents' abilities. In conclusion, the PPQ-8 by Rasch analysis is recommended for future use to evaluate the clinical severity of PP.